Evaluating tolerability of resistant starch 2, alone and in combination with minimally fermented fibre for patients with irritable bowel syndrome: a pilot randomised controlled cross-over trial. (21st February 2022) - So, Daniel; Yao, Chu K.; Gibson, Peter R.; Muir, Jane G.
Abstract: Resistant starch 2 (RS2) may offer therapeutic value to irritable bowel syndrome (IBS) patients particularly in combination with minimally fermented fibre, but tolerability data are lacking. The present study evaluated the tolerability of RS2, sugarcane bagasse and their combination in IBS patients and healthy controls. Following baseline, participants consumed the fibres in escalating doses lasting 3 d each: RS2 (10, 15 and 20 g/d); sugarcane bagasse (5, 10 and 15 g/d); and their combination (20, 25 and 30 g/d). Gastrointestinal symptoms were assessed daily. Six IBS patients and five controls were recruited. No differences in overall symptoms from baseline were found across the fibre doses (IBS, P = 0⋅586; controls, P = 0⋅687). For IBS patients, all RS2 doses led to increased bloating. One IBS patient did not tolerate the low combination dose and another the high sugarcane bagasse dose. Supplementation of RS2 ≤ 20 g/d caused mild symptoms and was generally tolerated in IBS patients even when combined with minimally fermented fibre.